Learning to care: medical students’ reported value and evaluation of palliative care teaching involving meeting patients and reflective writing - Erica Borgstrom (BMC Medical Education, 2016)
Abstract Background Over recent years there has been an increase in teaching of both palliative care and reflective practice in UK medical schools. The palliative care teaching at the University of Cambridge School of Clinical Medicine is multi-faceted and involves students writing reflective essays after individually meeting patients approaching the end of life during their final year general practice and hospital medicine placements. This paper draws on two studies examining this teaching element to analyse what the students found valuable about it and to comment on the practice of meeting patients and subsequent reflective writing. Methods Two studies have explored students’ perceptions of these course components. The first was a thematic analysis of 234 reflective essays from 123 students written in 2007-2008, including examining what students wrote about the exercise itself. The second project involved a semi-structured questionnaire that students completed anonymously; this paper reports on the free text elements of that study [sample size =107]. Since similar themes were found in both studies, the coding structures from each project were compared and combined, enabling triangulation of the findings around what the students found valuable from the palliative care teaching involving meeting patients and reflective writing. Results Overall, students reported that these components of the palliative care teaching are valuable. Four main themes were identified as aspects that students valued: (1) dedicated time with patients, (2) learning about wider elements of treatment and holistic care, (3) practicing communication skills, and (4) learning about themselves through reflective writing. Some students expressed a dislike for having to formally write a reflective essay. Conclusion It is possible to arrange for all of the medical students to individually meet at least two patients receiving palliative or end of life care. Students found these encounters valuable and many wrote about the benefit of formally writing about these experiences. Students reported finding this model useful in widening their skill-set and understanding of palliative care.